Hip Sublime : Beat Writers and the Classical Tradition - Rosen, Ralph Mark; Murnaghan, Sheila, 1951-; Project Muse. (Columbus : The Ohio State University Press, 2018)
"With essays that cover canonical Beat authors such as Allen Ginsberg, Jack Kerouac, and William Burroughs as well as less well-known figures like Kenneth Rexroth, Ed Sanders, and Diane di Prima, this volume focuses on the Beat movement's appropriation of the Greek and Latin classics as a formative element of their literary movement"--
Beats visiting hell: katabasis in Beat literature / Stephen Dickey -- "Thalatta, Thalatta!": Xenophon, Joyce, and Kerouac / Christopher Gair -- "The final fix" and "The transcendent kingdom": the quest in the early work of William S. Burroughs / Loni Reynolds -- The invention of sincerity: Allen Ginsberg and the philology of the margins / Matthew Pfaff -- Radical brothers-in-arms: Gaius and Hank at the racetrack / Marguerite Johnson -- Riffing on Catullus: Robert Creeley's poetics of adultery / Nick Selby -- Sappho comes to the Lower East Side: Ed Sanders, the sixties avant-garde, and fictions of Sappho / Jennie Skerl -- Robert Duncan and Pindar's dance / Victoria Moul -- Kenneth Rexroth: Greek anthologist / Gideon Nisbet -- Philip Whalen and the classics: "A walking grove of trees" / Jane Falk -- Troubling classical and Buddhist traditions in Diane di Prima's Loba / Nancy M. Grace and Tony Trigilio -- Towards a post-Beat poetics: Charles Olson's localism and the second sophistic / Richard Fletcher -- Afterword: "Standing at a juncture of planes" / Nancy M. Grace and Jennie Skerl.
Description based on print version record.
Keywords: Classical literature -- Influence; Beats (Persons); Authors, American; American literature; LITERARY CRITICISM -- Ancient & Classical; LITERARY CRITICISM -- American -- General; Beat generation; Litterature ancienne -- Influence; Litterature americaine -- 20e siecle -- Histoire et critique; Écrivains americains -- 20e siecle; Beatniks; Classical literature -- Influence; American literature -- 20th century -- History and criticism; Authors, American -- 20th century; Beats (Persons); Criticism, interpretation, etc; Electronic books